Local communities vulnerability to climate change and adaptation strategies in Bukavu in DR Congo - Bele, M.Y.; Sonwa, D.J.; Tiani, A.M. (SAGE Publications, 2014)
The analysis of vulnerabilities can help answer where and how society can best invest in vulnerability reduction. This study aimed at exploring vulnerability and adaptation strategies to climate change of local communities in Bukavu in DR Congo. Participatory action research was used in six villages from three collectivities around the Kahuzi Biega Park. Results showed that (a) perception of climate change depends on what people can see and feel about climate, (b) climate-related risks exacerbated existing problems and created new combinations of risks such as loss of livelihoods and deepening poverty cycle associated, (c) a range of adaptation measures was used or envisaged, and (d) implementation of those measures was hampered by a range of barriers. It is therefore imperative for climate change and climate variability measures to be taken seriously and for adaptation strategies to be integrated into all spheres of public policy making with focus on key economic development sectors.